2020
DOI: 10.1016/j.yebeh.2020.107437
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy-associated neurocognitive disorders (EAND) in an onchocerciasis-endemic rural community in Cameroon: A population-based case–control study

Abstract: Background: Epilepsy affects at least 50 million individuals worldwide, especially in sub-Saharan Africa (sSA). Cognitive impairment is common in people with epilepsy (PWE) yet, little is known on the burden of cognitive impairment in people with epilepsy in sSA. This study was thus designed to assess cognitive impairment in PWE or epilepsy-associated neurocognitive disorders (EAND) in a rural population in Cameroon. Methods: This was a case-control study including PWE and age/sex-matched healthy controls from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…The second important finding of our study is the confirmation of the finding of severe CI in PWE in the Mbam valley by Njamnshi et al 31 who reported 92.5% reduction of performance in executive function tests and 100% impairment of verbal fluency. In our study participants, 66% had severe frontal CI, while 29% showed severe global CI and 28% had severe episodic memory impairment.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The second important finding of our study is the confirmation of the finding of severe CI in PWE in the Mbam valley by Njamnshi et al 31 who reported 92.5% reduction of performance in executive function tests and 100% impairment of verbal fluency. In our study participants, 66% had severe frontal CI, while 29% showed severe global CI and 28% had severe episodic memory impairment.…”
Section: Discussionsupporting
confidence: 86%
“…CI might thus be a consequence of repeated seizures, and this is consistent with the fact that EEG abnormalities are mainly in the frontal and temporal lobe. However, the role of ASM and onchocerciasis infection in CI in our study subjects cannot be ruled out, especially given that the case‐control study in Bilomo 31 reported CI in controls, although the issue of using culturally sensitive neuropsychological tests remains to be resolved. ASM might have contributed to CI as phenobarbital use was associated with a lower cognitive score than carbamazepine, suggesting a potentiation of the cognitive disorders by phenobarbital, known for its long‐term side effects on attention mechanisms 37 …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on these results, it appears that infection with O. volvulus may impact executive functions more than motor functions. In line with these observations, a recent study conducted in the onchocerciasis-endemic village of Bilomo in Cameroon found a high prevalence of both executive function deficits (92.5% among PWE vs 40.0% among controls; p < 0.001) and decreased verbal fluency (100% among PWE vs 45% among controls; p < 0.001), with a longer duration of residence in the village being associated with poorer neurocognitive performance (Njamnshi et al, 2020). This suggests that exposure to O. volvulus may induce cognitive impairment which could be exacerbated by the development of epilepsy.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, previous studies revealed that persons with OAE often show signs of cognitive impairment (Colebunders et al, 2018a, b;Siewe Fodjo et al, 2019a, b, c). Furthermore, in a recent case-control study in onchocerciasisendemic communities in Cameroon in Cameroon, we found that cognitive impairment (assessed using a comprehensive neuropsychological test battery) was significantly more prevalent in persons with epilepsy (PWE) than in age-and sexmatched controls (Njamnshi et al, 2020). However, it is still unclear whether the cognitive symptoms observed in persons with OAE preceded seizure onset, or were solely consequences of the repeated epileptic episodes.…”
Section: Introductionmentioning
confidence: 91%